2018
DOI: 10.2112/jcoastres-d-17-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

The Longshore Transport Enigma and Analysis of a 10-Year Record of Wind-Driven Nearshore Currents

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They found that during intense sea breeze events the alongshore currents significantly increase inside the surf and swash zones. Therefore, in the present case of a coast subjected to sea breeze conditions, the highly oblique winds (see Figure 2a) play a major role in driving longshore currents and consequently longshore transport [28][29][30]. Torres-Freyermuth et al [22] conducted a field experiment to characterize the nearshore circulation during both intense local sea breeze events and synoptic Norte events.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…They found that during intense sea breeze events the alongshore currents significantly increase inside the surf and swash zones. Therefore, in the present case of a coast subjected to sea breeze conditions, the highly oblique winds (see Figure 2a) play a major role in driving longshore currents and consequently longshore transport [28][29][30]. Torres-Freyermuth et al [22] conducted a field experiment to characterize the nearshore circulation during both intense local sea breeze events and synoptic Norte events.…”
Section: Study Areamentioning
confidence: 99%
“…They found that during intense sea breeze events the alongshore currents significantly increase inside the surf and swash zones. Therefore, in the present case of a coast subjected to sea breeze conditions, the highly oblique winds (see Figure 2a) play a major role in driving longshore currents and consequently longshore transport [28][29][30].…”
Section: Study Areamentioning
confidence: 99%
“…However, wind stress may be more important for nearshore transport during wet weather or in other regions. For example, in Melbourne Beach, FL, where hurricanes are common, the correlation of wind stress with waves explained net sediment transport better than waves alone …”
Section: Resultsmentioning
confidence: 99%
“…waves explained net sediment transport better than waves alone. 50 Applications for Beach Management. Here tracer was modeled on norovirus because quantitative microbial risk assessment has found norovirus to be the greatest contributor to GI illness likelihood in marine swimmers, 51,52 but EPA guidelines use cultured Enterococcus as the basis for beach advisories for marine waters.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The wind-driven current takes place in the coastal area of Ie Meulee proved by the same dominant current direction as the wind movements which the speed ranged from 0.1-0.3 m/s. The winddriven current is the main factor in triggering the local transport in the coastal area related to the sediment transport beneath the first breaking-wave crest distributed by longshore current (Burnette and Dally, 2018).…”
Section: Sea Current Patterns In the Ie Meulee Watersmentioning
confidence: 99%